Bifidobacterium animalis subsp lactis HN019 presents antimicrobial potential against periodontopathogens and modulates the immunological response of oral mucosa in periodontitis patients - Invernici, Marcos M. (2020)
Objective To evaluate the effects of Bifidobacterium animalis subsp. lactis HN019 (HN019) on clinical periodontal parameters (plaque accumulation and gingival bleeding), on immunocompetence of gingival tissues [expression of beta-defensin (BD)-3, toll-like receptor 4 (TLR4), cluster of differentiation(CD)-57 and CD-4], and on immunological properties of saliva (IgA levels) in non-surgical periodontal therapy in generalized chronic periodontitis (GCP) patients. Adhesion to buccal epithelial cells (BEC) and the antimicrobial properties of HN019 were also investigated. Materials and methods Thirty patients were recruited and monitored clinically at baseline (before scaling and root planing-SRP) and after 30 and 90 days. Patients were randomly assigned to Test (SRP+Probiotic, n = 15) or Control (SRP+Placebo, n = 15) group. Probiotic lozenges were used for 30 days. Gingival tissues and saliva were immunologically analyzed. The adhesion of HN019 with or without Porphyromonas gingivalis in BEC and its antimicrobial properties were investigated in in vitro assays. Data were statistically analyzed (p<0.05). Results Test group presented lower plaque index (30 days) and lower marginal gingival bleeding (90 days) when compared with Control group. Higher BD-3, TLR4 and CD-4 expressions observed in gingival tissues in Test group than in Control group. HN019 reduced the adhesion of P. gingivalis to BEC and showed antimicrobial potential against periodontopathogens. Conclusion Immunological and antimicrobial properties of B. lactis HN019 make it a potential probiotic to be used in non-surgical periodontal therapy of patients with GCP.